Love and Marriage in Georg Simmel’s Work. A Nineteenth-Century Post-Romantic? - Rodríguez Morales, Zeyda (Simmel Studies, 2021)
The main purpose of this text is to address two crucial aspects of Georg Simmel's work: the originality of his sociological approach, as well as his conception of love feelings. To undertake this task, I will take as a frame of reference a fundamental cultural construction of his time, romantic love. I will try to show that although some of Simmel's ideas about love can be seen as a product of the prevailing mentality, others do not fit with this imaginary, and in my opinion, they are avant-garde and post-romantic because they freely propose different parameters to think, feel and engage into amorous relationships.